Пошаговое объяснение:
( (4*x-5)*4+18):6=30-5*5
(16х-20+18):6=30-25
(16х-2):6=5
16х-2=5*6
16х-2=30
16х=30+2
16х=32
х=32:16
х=2
( (4*2-5)*4+18):6=30-5*5
(3*4+18):6=5
30:6=5
5=5
12 : (4/5х) = 20 : 1/4 5/6 = 15/(2х - 3)
4/5х * 20 = 12 * 1/4 5 : 6 = 15 : (2х - 3)
80/5х = 12 : 4 6 * 15 = 5 * (2х - 3)
16х = 3 90 = 10х - 15
х = 3 : 16 90 + 15 = 10х
х = 3/16 105 = 10х
х = 105 : 10
х = 10,5
(15/2)/(9/2) = х - 3/25
15/2 * 2/9 = х - 3/25
15/9 = х - 3/25
5/3 + 3/25 = х
х = 125/75 + 9/75 = 134/75 = 1 59/75
(16х-2):6=5
16х-2=30
16х=32
Х=2